The Relation of the Plasma Ascorbic Acid to Bone MineralDensity in Women Referring to Jami Clinic 2006 Tehran, Iran: Ascorbic acid and bone mineral density - Behrooz Jannat,; Mohammad-Reza Oveisi,; Naficeh Sadeghi,; Mannan Hajimahmoodi,; Saeed Javadi,; Molouk Hadjibabaie,; Ahmad-Reza Jamshidi,; Majid Korouji,; Masoomeh Behzad, (Iranian Journal of Pharmaceutical Sciences, 2008)
Osteoporosis is a silent epidemy of today's world, and is also a prevalent problem of health in Iran. The role of nutrients such as ascorbic acid, a key antioxidant vitamin,in this disease has recently attracted researchers' attention. In this study, we studied the relation between plasma ascorbic acid concentration and bone mineral density (BMD) in women referring to Jami clinic, Tehran, Iran. The study was performed in 200 participants who underwent a fasting blood withdrawal. The control group(n=76; 39.6%) were normal in both lumbar spine (L1-L4) and femoral neck (T-score ≥-1).Femur T-score was considered as criterion in selection of the patient group. Seventy six subjects (39.6%) with T-score>-1 were known as total patient group (TP). TPwere divided into mild patients (M; -1>T-score -1.7), and severe patients (S; -1.7>T-score). Plasma ascorbic acid levels were analyzed by ferric reducing ascorbic acidconcentration, a spectrophotometric assay. Mean SD plasma level of ascorbic acidwas 74.55±67.60 µM in control group, 54.73±46.65 M in TP(T-score<-1),47.31±36.07 M in S patient group (T-score -1.7), and 70.28±61.58 M in M patients(-1>T-score > -1.7), resectively. Our results support an association between plasmalevels of ascorbic acid and BMD. The results showed that: 1) plasma levels of ascorbicacid were lower in patients with osteoporosis than in control; 2) the difference washigher between control and group S (T-score ≤-1.7) who had more acute diseasethan group M (-1.7<T-score <-1) who had milder disease; and finally 3) femoral neckT-score showed a positive and significant correlation with plasma levels of ascorbic acid in all participants.